2015
DOI: 10.1145/2816795.2818117
|View full text |Cite
|
Sign up to set email alerts
|

Fast multiple-fluid simulation using Helmholtz free energy

Abstract: Figure 1: Egg Mixture. In simulating the stirring of 3 eggs by a blender, the resulting simulation presents visually plausible mixing results. This mixing effect is achieved using our novel "extended mobility" formulation of the Navier-Stokes-Cahn-Hilliard Model. AbstractMultiple-fluid interaction is an interesting and common visual phenomenon we often observe. In this paper, we present an energybased Lagrangian method that expands the capability of existing multiple-fluid methods to handle various phenomena, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
49
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 56 publications
0
49
0
Order By: Relevance
“…Park et al [2008] showed that energy can be used to drive multi-fluid simulations, and adopted the Cahn-Hilliard equation to handle both miscible and immiscible fluids using a lattice Boltzmann method (LBM). Their approach was later extended by Yang et al [2015], who achieved impressive results for problems such as extraction (i.e. separating a substance from a mixture) and mixing of an egg yolk and egg white.…”
Section: Multi-fluid Simulationmentioning
confidence: 99%
See 4 more Smart Citations
“…Park et al [2008] showed that energy can be used to drive multi-fluid simulations, and adopted the Cahn-Hilliard equation to handle both miscible and immiscible fluids using a lattice Boltzmann method (LBM). Their approach was later extended by Yang et al [2015], who achieved impressive results for problems such as extraction (i.e. separating a substance from a mixture) and mixing of an egg yolk and egg white.…”
Section: Multi-fluid Simulationmentioning
confidence: 99%
“…In this section, we first review the energy-driven multi-fluid simula-tion proposed by Yang et al [2015], and then show how to extend this framework to handle other phases.…”
Section: Phase-field Multi-materials Simulationmentioning
confidence: 99%
See 3 more Smart Citations